Coercive Control in the Courtroom: the Legal Abuse Scale (LAS) - Gutowski, Ellen R. (Journal of family violence, 2023)
Intimate partner violence (IPV) survivors seeking safety and justice for themselves and their children through family court and other legal systems may instead encounter their partners’ misuse of court processes to further enact coercive control. To illuminate this harmful process, this study sought to create a measure of legal abuse. We developed a list of 27 potential items on the basis of consultation with 23 experts, qualitative interviews, and existing literature. After piloting these items, we administered them to a sample of 222 survivor-mothers who had been involved in family law proceedings. We then used both exploratory factor analysis (EFA) and Rasch analysis (RA) to create a final measure. Analyses yielded the 14-item Legal Abuse Scale (LAS). Factor analysis supported two subscales: Harm to Self/Motherhood (i.e., using the court to harm the survivor as a person and a mother) and Harm to Finances (i.e., using the court to harm the survivor financially). The LAS is a tool that will enable systematic assessment of legal abuse in family court and other legal proceedings, an expansion of research on this form of coercive control, and further development of policy and practice that recognizes and responds to it.